REPAIR OF GARBAGE CARTS AS PART OF UPSTREAM SIDE WASTE MANAGEMENT IN THE PERMATA MILLAN JAKARTA ENVIRONMENT: PERBAIKAN GEROBAK SAMPAH SEBAGAI BAGIAN DARI MANAJEMEN SAMPAH SISI HULU DI LINGKUNGAN PERMATA PENGGILINGAN JAKARTA - Cahyo Wibowo; Daud Surbakti; Fathan Mubina Dewadi (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Garbage is a very complicated problem and will occur continuously throughout the world, inseparable in Indonesia in general and especially in the capital city . In terms of waste management in Jakarta so far, it is still not good, considering that the waste management handled by the local government can only be seen from the Temporary Waste Disposal Plant to the Final Waste Disposal Plant. This can be seen from the condition of the garbage carts which are very unfit for the size of a Metropolitan City, Jakarta is an icon and barometer of all cities in Indonesia, but the condition of the garbage transport equipment does not reflect a big city that is identical with everything that is clean and tidy. One part of waste management management is a garbage cart, the management of a garbage cart does not reflect that a garbage cart is for the capital city. Garbage carts are rickety, smelly, dirty, dirty, the transported garbage falls scattered, the garbage collectors are also dirty and smelly without being equipped with makeshift tools and makeshift clothes